1981
DOI: 10.1016/0304-3959(81)90190-1
|View full text |Cite
|
Sign up to set email alerts
|

The deafferentation syndrome in monkeys: Dysesthesias of spinal origin

Abstract: Chronic thoracic spinal lesions were surgically placed in 35 monkeys of 6 different species. In a very large percent of the cases, a bizarre behavioral pattern was released, which persisted for many months of observation. This syndrome was one in which the monkey severely attacked an hypoalgesic area of the body, namely, the leg. The syndrome resulted from contralateral anterolateral cordotomy or hemisection. It was very similar to the deafferentation syndrome which results from extensive dorsal rhizotomies. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…Several laboratories have reported the incidence of autophagia of the contralesional hindlimb after unilateral thoracic hemisection from 10% to more than 50% of the subjects. 6,[26][27][28] In the current study that utilized a unilateral C5 contusion, no rats displayed autophagia.…”
Section: Discussionmentioning
confidence: 99%
“…Several laboratories have reported the incidence of autophagia of the contralesional hindlimb after unilateral thoracic hemisection from 10% to more than 50% of the subjects. 6,[26][27][28] In the current study that utilized a unilateral C5 contusion, no rats displayed autophagia.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, dysesthesias are commonly found in body parts in which there is reduced or no sensory response to peripheral somatic stimulation (e.g., in hypoesthesia, hypoalgesia, anesthesia, analgesia). Earlier studies in monkeys have shown that monkeys can appear to develop hyperesthesia at the border of the sensory level after chronic spinal cord transections [60], and occasional abnormal, compulsive, self-directed behaviors have been reported after thoracic spinal cord lesions [61,62]. The studies of other investigators report that animals displayed compulsive rubbing, depilation, and biting of areas within the hypoalgesic dermatomes after mid-thoracic anterolateral cordotomy or hemisection.…”
Section: Contributions and Implications: Safety Assessmentmentioning
confidence: 98%
“…Note that these clinical signs occur on the side of the animal that does not display motor deficits. Levitt [64] concluded that the "deafferentation syndrome" was released by interrupting spinothalamic tracts, and that the incidence was genetically variable (incidence of 31% in a multispecies group to 95% in a group of 19 stump-tailed macaques), and that some of the variability might be related to variability in the location of the spinothalamic tracts (sometimes in the posterolateral funiculus and sometimes in the ipsilateral anterolateral funiculus) [61,64]. In those earlier studies, monkeys that had sensorimotor deficits did not display disruptions of activity level, feeding, grooming (normal dermatomes), libido, vocalization, or social behavior.…”
Section: Contributions and Implications: Safety Assessmentmentioning
confidence: 99%
“…61 Lesions of the anterolateral spinal column in monkeys and rats have been shown to produce caudally directed overgrooming/autotomy. 49,51 Christensen and Hulsebosch 50,62 have described a model for neuropathic pain either at or below the level of injury. Their rats developed mechanical and thermal allodynia after a cord hemisection.…”
Section: Experimental Modelsmentioning
confidence: 99%